PENGARUH JUMLAH BIRO PERJALANAN WISATA, JUMLAH KUNJUNGAN WISATAWAN DAN PAJAK HOTEL RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BADUNG - Paramacintya, Ni Made Sri Yundari; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
PAD is an important benchmark to determine the level of regional capability in implementing regional autonomy in a real and responsible way. Several tourism sector activities can affect local revenue in Badung regency. The data of this research are secondary data obtained from BPS of Badung, Bali Province and BPKAD Badung. This research uses data analysis technique that is path analysis. The results of this study as follows: 1) the number of travel agency has positive and insignificant effect on hotel restaurant tax in Badung; 2) the number of tourist visit has positive and significant influence to hotel restaurant tax in Badung; 3) the number of tour travel agent influences positive and insignificant to the local revenue in Badung, 4) the number of tourist visit has positive and significant influence to the local income in Badung; 5) hotel restaurant tax has positive and significant effect to the local revenue in Badung; 6) travel tour does not affect the local revenue through the hotel restaurant tax in Badung, 7) the number of tourist visits have a positive and significant effect on the local revenue through hotel restaurant tax in Badung. Keywords: travel agency, tourist visit, hotel restaurant tax, local revenue